2004
DOI: 10.1002/mma.545
|View full text |Cite
|
Sign up to set email alerts
|

Global existence of the radially symmetric solutions of the Navier–Stokes equations for the isentropic compressible fluids

Abstract: We study the isentropic compressible Navier–Stokes equations with radially symmetric data in an annular domain. We first prove the global existence and regularity results on the radially symmetric weak solutions with non‐negative bounded densities. Then we prove the global existence of radially symmetric strong solutions when the initial data ρ0, u0 satisfy the compatibility condition for some radially symmetric g ∈ L2. The initial density ρ0 needs not be positive. We also prove some uniqueness results on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 12 publications
0
52
0
Order By: Relevance
“…He showed that there is no global classical solution to the Cauchy problem for the isentropic compressible Navier-Stokes equations with compactly supported initial density and velocity. On the other hand, Choe and the second author [5] obtained a global existence result on radially symmetric strong solutions of the isentropic compressible Navier-Stokes equations in bounded and unbounded annular domains. Hence it is very likely that the methods in this paper and [5] can be combined to prove the global existence of radially symmetric classical solutions with nonnegative densities.…”
Section: Remark 12 From the Continuity Equation (11) It Follows Imentioning
confidence: 99%
See 1 more Smart Citation
“…He showed that there is no global classical solution to the Cauchy problem for the isentropic compressible Navier-Stokes equations with compactly supported initial density and velocity. On the other hand, Choe and the second author [5] obtained a global existence result on radially symmetric strong solutions of the isentropic compressible Navier-Stokes equations in bounded and unbounded annular domains. Hence it is very likely that the methods in this paper and [5] can be combined to prove the global existence of radially symmetric classical solutions with nonnegative densities.…”
Section: Remark 12 From the Continuity Equation (11) It Follows Imentioning
confidence: 99%
“…On the other hand, Choe and the second author [5] obtained a global existence result on radially symmetric strong solutions of the isentropic compressible Navier-Stokes equations in bounded and unbounded annular domains. Hence it is very likely that the methods in this paper and [5] can be combined to prove the global existence of radially symmetric classical solutions with nonnegative densities. This issue will be studied in a separated paper.…”
Section: Remark 12 From the Continuity Equation (11) It Follows Imentioning
confidence: 99%
“…On the existence and regularity of weak solutions with density connecting to vacuum continuously in 1D, please refer to [20]. During the pass two decades, Salvi, Choe, Kim and Jiang et al made great progress towards the local or global existence of strong (classical) solutions with vacuum, see [27,2,4,5,7,3]. Particularly, Choe and Kim in [5] showed that the radially symmetric strong solutions exist globally in time for γ 2 and N 2.…”
Section: Introductionmentioning
confidence: 99%
“…They showed in [12] that if Ω is a bounded domain in R 3 , π = π(·) ∈ C 2 [0, ∞), ρ 0 ∈ H 2 (Ω), u 0 ∈ H 1 0 (Ω) ∩ H 2 (Ω) and the compatibility condition −μ u 0 + ∇π(ρ 0 ) = ρ 1/2 0 g, for some g ∈ L 2 (Ω), (1.3) is satisfied, then there exists a unique local strong solution (ρ, u) to the initial boundary value problem. Independently of their work, H. Choe and H. Kim [3,13], Y. Cho, H. Choe and H. Kim [4] proved a similar existence result when Ω is either a bounded domain or the whole space and the compatibility condition (1.3) is satisfied. This is somewhat surprising because in the context of the compressible Navier-Stokes or Euler equations, there have been many works concerning the existence of solution with compactly supported initial data.…”
Section: Introduction and Main Resultsmentioning
confidence: 69%